Context-Dependent Tumorigenic Effect of Testis-Specific Mitochondrial Protein Tiny Tim 2 in Drosophila Somatic Epithelia - Cristina Molnar; Anxela Louzao; Cayetano Gonzalez (Cells, 2020)
We have undertaken a study towards understanding the effect of ectopic expression of testis proteins in the soma in Drosophila. Here, we show that in the larval neuroepithelium, ectopic expression of the germline-specific component of the inner mitochondrial translocation complex tiny tim 2 (ttm2) brings about cell autonomous hyperplasia and extension of G2 phase. In the wing discs, cells expressing ectopic ttm2 upregulate Jun N-terminal kinase (JNK) signaling, present extended G2, become invasive, and elicit non-cell autonomous G2 extension and overgrowth of the wild-type neighboring tissue. Ectopic tomboy20, a germline-specific member of the outer mitochondrial translocation complex is also tumorigenic in wing discs. Our results demonstrate the tumorigenic potential of unscheduled expression of these two testis proteins in the soma. They also show that a unique tumorigenic event may trigger different tumor growth pathways depending on the tissular context.